2016
DOI: 10.1111/mmi.13373
|View full text |Cite
|
Sign up to set email alerts
|

Vital and dispensable roles of Plasmodium multidrug resistance transporters during blood‐ and mosquito‐stage development

Abstract: Multidrug resistance (MDR) proteins belong to the B subfamily of the ATP Binding Cassette (ABC) transporters, which export a wide range of compounds including pharmaceuticals. In this study, we used reverse genetics to study the role of all seven Plasmodium MDR proteins during the life cycle of malaria parasites. Four P. berghei genes (encoding MDR1, 4, 6 and 7) were refractory to deletion, indicating a vital role during blood stage multiplication and validating them as potential targets for antimalarial drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…This confirmed our PCR results showing that Pb ANKA_0614600 and Pb ANKA_0942100 are probably essential (Figures S2–S4). Additionally, the candidate apicoplast membrane transporter, Pb ANKA_0401200, was reported to be refractory to deletion by Rijpma et al (). We recovered parasites from only one of three transfections with the Pb ANKA_0401200 KO construct, and although our PCR results indicated that integration had occurred (Figure S1), we set out to validate our positive result by Southern blot (Figures S5–S6).…”
Section: Resultsmentioning
confidence: 99%
“…This confirmed our PCR results showing that Pb ANKA_0614600 and Pb ANKA_0942100 are probably essential (Figures S2–S4). Additionally, the candidate apicoplast membrane transporter, Pb ANKA_0401200, was reported to be refractory to deletion by Rijpma et al (). We recovered parasites from only one of three transfections with the Pb ANKA_0401200 KO construct, and although our PCR results indicated that integration had occurred (Figure S1), we set out to validate our positive result by Southern blot (Figures S5–S6).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, of all nineteen targeted pumps, eleven were shown to be refractory to gene deletion (Table S1). In addition to the four MDRs (MDR1, MDR4, MDR6, and MDR7) 22, these include the putative cation transporting ATPase, ATP4, (S. Kenthirapalan, K. Matuschewski, T.W.A. Kooij, unpublished data), ATP6 45 and the V-type proton ATPase subunit G 46, ABCI3, and four predicted aminophospholipid transporters 23.…”
Section: Resultsmentioning
confidence: 99%
“…Due to more efficient experimental and computational methods and access to the entire in vivo life cycle, the majority of such studies have been performed using murine malaria model species, notably Plasmodium berghei , and have focussed on single MTPs (Table S1). Two of our most recent studies have more than doubled the number of targeted genes, and have generated loss-of-function mutants in both P. falciparum and P. berghei 2223. A systematic study of the MDR family demonstrated that four of seven members fulfil essential functions during blood-stage development, highlighting these as potential drug targets 22.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have for the most part focused on essentiality and growth rate phenotypes in the asexual blood stage of the parasite and have ranged from those which specifically targeted subsets of transporter genes to the large‐scale knockout screen of 2578 P. berghei genes (Bushell et al ., ). The transporters targeted by the small‐scale screens have included the genes encoding 35 ‘orphan transporters’ (Kenthirapalan et al ., ), ATP‐binding cassette (ABC) type pumps (Rijpma et al ., ), and transporters predicted to localise to the membranes of the apicoplast (Sayers et al ., ).…”
Section: The Plasmodium Transportomementioning
confidence: 99%